The ROLE OF GENDER IN SHAPING STUDENTS’ LANGUAGE LEARNING PERFORMANCE IN EFL CONTEXT: A LITERATURE STUDY - Saragih, Enni Erawati; Adeliya, Nurlaila; Maisalinia, Ria (Jurnal Obor Penmas: Pendidikan Luar Sekolah, 2026)
The purpose of this study is to investigate whether gender-based differences influence students’ speaking performance in EFL contexts. Several preliminary studies have shown mixed results, indicating inconsistencies in identifying which gender dominates in speaking between male and female students. Several studies show that female students perform better in speaking, while others highlight the strengths of male students in certain aspects. This study adopts a literature study that involves several steps, including searching for and discovering relevant data, and formulating conclusions based on the findings. The results reveal that female students tend to excel in most aspects of speaking performance, such as fluency, accuracy, intonation, vocabulary, and confidence. Therefore, it can be inferred that female students generally show stronger speaking abilities than male students. The results are expected to offer constructive insights for English teachers to better support both male and female students in improving their speaking abilities. Furthermore, the implications of the results propose recommendations for teachers to apply more effective and inclusive methods in English language classrooms.